Thermal Analysis of Power Electronic Devices Used in Renewable Energy Systems - Albarbar, Alhussein (Springer International Publishing, 2018)
Provides a detailed explanation of modeling steps and verification through experimental data Offers practical and easy-to-follow steps for readers to develop realistic finite element modeling techniques Explains how to accurately predict thermal characteristics of power electronic devices in typical environmental conditions This book analyzes the thermal characteristics of power electronic devices (PEDs) with a focus on those used in wind and solar energy systems. The authors focus on the devices used in such applications, for example boost converters and inverters under different operating conditions. The book explains in detail finite element modeling techniques, setting up measuring systems, data analysis, and PEDs' lifetime calculations. It is appropriate reading for graduate students and researchers who focus on the design and reliability of power electronic devices.